EXPLORING READING PROCESS OF TAIWANESE STUDENTS: USING MISCUES ANALYSIS - Sitorus, Friska RIA; Silalahi, Wolter Parlindungan; Lin, Huei (PEOPLE: International Journal of Social Sciences, 2015)
The purpose of this study was to investigate the reading process of readers’ miscues in reading a text. Ken Goodman first coined the term to describe an observed response in the reading process that does not match the expected response (Goodman, 1973). The term "miscue," rather than "error" or "mistake" is used to avoid judgments. Good miscues do not change the meaning of the sentence or story and are called high-quality miscues. On the other hand, miscues that do not make sense are called low-quality miscues. Five Taiwanese undergraduate students were recruited to participate in this study. They were all from and demonstrated similar English competency. The participants were asked to read an unfamiliar and unpracticed text. This study used interview and retelling guide (including both un-added and added retelling) to collect data. Reading miscue analysis was employed to analyze Taiwanese students’ reading style and error patterns. The results found that all readers made more than 25 miscues in reading. All the readers made the miscues of dialect and insertion. Moreover, some readers made nonwords substitutions and repetitions miscues without affecting their understanding of the text.